BIO-MOLECULAR STUDY OF JEMBRANA VIRUS: AS BASIC DEVELOPMENT OF TISSUE CULTURE VACCINE - Tanaya, I Wayan Masa (Buletin Veteriner Udayana, 2016)
Phatogenesis and bio-molecular of jembrana disease virus (JDV) only attack B-cell as a target, causing no produced antibody until 2-3 months post infection. Significantly increasing the number of CD8+ T-cells and significantly decreasing of CD4+ T-cells during acute phase affecting in decreased of CD8+:CD4+ ratio, that resulting in increasing sensitifity of animal to secunder infection. Nine bali cattle used in this study grouped based on infection status related to sample collected. Seven bali cattle infected by JDV isolate Tabanan/87 and two other cattle infected by BIV isolate R29, as a negative control (Non-JDV infected cattle). Samples tested of cellular identity and targeted cell, cellular immunity and cytokine expressions. Samples tested by flow cytometry and analyzed by variance. The result showed that the change of T-cell sub-population related to recovery of JVD infection strengthen the role of cellular immunity in a process of healing Jembrana disease. Evidences of enhancement of cytokine gene expressions produced by CDB T-cell mainly by IFN-g and IL-2, indicated the importance of those genes in an infection process and recovery.
Keywords: virus penyakit jembrana; sapi bali; sitokin; in vitro; Jembrana disease virus; bali cattle; cytokine; in vitro